2000
DOI: 10.1016/s0022-5347(05)68003-2
|View full text |Cite
|
Sign up to set email alerts
|

Radical Retropubic Prostatectomy: Bladder Neck Preservation Versus Reconstruction

Abstract: There are no statistically significant differences in return of urinary continence, bladder neck contracture rates or positive margins between bladder neck preservation and excision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
3

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(61 citation statements)
references
References 21 publications
1
57
0
3
Order By: Relevance
“…Shelfo et al [6] studied 365 patients having BN-preserving radical retropubic prostatectomy (RRP) and observed that 88% were continent at 6 months with 7% having a +SM at BN. Poon et al [7] retrospectively studied 101 patients having BN-sparing RRP and compared continence rates with patients having BN reconstruction either with a racket handle repair or an anterior bladder tube reconstruction. High continence rates 6 93% were achieved regardless of the BN approach used.…”
Section: Discussionmentioning
confidence: 99%
“…Shelfo et al [6] studied 365 patients having BN-preserving radical retropubic prostatectomy (RRP) and observed that 88% were continent at 6 months with 7% having a +SM at BN. Poon et al [7] retrospectively studied 101 patients having BN-sparing RRP and compared continence rates with patients having BN reconstruction either with a racket handle repair or an anterior bladder tube reconstruction. High continence rates 6 93% were achieved regardless of the BN approach used.…”
Section: Discussionmentioning
confidence: 99%
“…57,75 Other authors have confirmed there is no negative impact on margin status following bladder neck preserving surgery but they have failed to show any significant improvement on return of urinary continence 57 or bladder neck contracture. 59 …”
Section: Surgical Techniquementioning
confidence: 99%
“…Several other investigators have concentrated on BN preservation as a method to improve postoperative continence, with controversial results regarding the contribution of the technique to both postoperative continence and the oncological outcome. 9,12,22,23 Urethral and BN suspension by various methods (e.g., stitches and slings) has been used in the management of stress incontinence for several years. 24 Walsh and Partin 25 described a technical refinement that divided the dorsal venous complex (DVC) with minimal blood loss while taking care not to injure the striated sphincter.…”
Section: Discussionmentioning
confidence: 99%